Optimal duration of dual antiplatelet therapy after second-generation drug-eluting stent implantation in patients with diabetes: The SECURITY (Second-Generation Drug-Eluting Stent Implantation Followed By Six- Versus Twelve-Month Dual Antiplatelet Therapy)-diabetes substudy. (15th March 2016) - Tarantini, Giuseppe; Nai Fovino, Luca; Tellaroli, Paola; Chieffo, Alaide; Barioli, Alberto; Menozzi, Alberto; Frasheri, Arian; Garbo, Roberto; Masotti-Centol, Monica; Salvatella, Neus; Dominguez, Juan Francisco Oteo; Steffanon, Luigi; et al.
Abstract: Background/Objectives: The randomized SECURITY (Second-Generation Drug-Eluting Stent Implantation Followed by Six- Versus Twelve-Month Dual Antiplatelet Therapy) trial showed the non-inferiority of 6 vs. 12-month DAPT after percutaneous coronary intervention (PCI) with second-generation DES in a low-risk population. Nevertheless, diabetes mellitus (DM) remained a major predictor of adverse cardiovascular events. We aimed to assess the interaction between DAPT duration and outcome in DM patients. Methods: All diabetic patients included in the SECURITY trial treated by second-generation DES PCI were analyzed. The primary endpoint was a composite of cardiac death, myocardial infarction (MI), stroke, definite or probable stent thrombosis (ST), or Bleeding Academic Research Consortium (BARC) type 3 or 5 bleeding at 12 months. The main secondary endpoint was a composite of cardiac death, MI, stroke, definite or probable ST, or BARC type 2, 3, or 5 bleeding at 24 months. Results: Four hundred-twenty nine DM patients received either 6 (n = 206) or 12 (n = 223) months of DAPT. The primary endpoint occurred in 3.9% and 5.4% of patients in the 6 and 12-month DAPT group, respectively (log-rank test p = 0.83). Similarly, no statistically significant difference in the secondary endpoint was observed between the two study groups (5.4% vs. 7.6%, p = 0.620). Stent thrombosis rate was low irrespective of DAPT duration at both 12 (0.5% vs. 0.4%; p = 0.804) and between 12 and 24 months of follow-up (0.5% vs. 0%, p = 0.291). At multivariable analysis, female gender (HR: 3.42; 95% CI 1.32–8.85; p = 0.011 and HR 2.28; 95% CI 1.09–4.75; p = 0.027) and insulin-treated diabetes mellitus (HR: 2.62; 95% CI 1.15–6.75; p = 0.004 and HR: 2.23; 95% CI 1.09–6.33; p = 0.003) were independent predictors of both primary and secondary endpoint. Conclusions: In diabetic patients treated by second-generation DES PCI, we failed to find any additional benefit of prolonging DAPT beyond 6 months, regardless of insulin-requiring status.